Исследование свойств целевой функции дискретного аргумента в задачах разрешения неоднозначности фазовых ГНСС наблюдений - Дицкий, И. В. (Weber, 2010)
The preliminary researches of the results of car rier-phase ambiguity resolution method which use direct enumeration are presented. Search method of quadratic form minimum is described.